STUDI KEPUASAN DAN LOYALITAS NASABAH TERHADAP PRODUK KPR SYARIAH DENGAN PENDEKATAN METODE NET PROMOTER SCORE - Ayu wandirara; Mulia Amrullah; Nila Nopianti; Ganjar Santika (Mumtaz Publishing, 2025)
The purpose of this study is to examine the level of satisfaction and loyalty among Sharia KPR customers in the Bumi Pakarangan Ciamis housing complex. Competition among banks has increased due to the growing interest of the public in Sharia-based KPR. Improving the quality of a product and service for business continuity is the main reason why the level of customer satisfaction and loyalty needs to continue to be evaluated for the sake of product and company sustainability. This study employs a quantitative method and utilizes primary data types. Data collection methods involved the distribution of online and offline questionnaires. The Net Promoter Score data analysis method was utilized for this analysis. According to the research findings, Sharia KPR products at Bumi Pakarangan Ciamis Housing have a Net Promoter Score value of 37. At the same time, the Loyalty variable's Net Promoter Score value is 29. This value is in the middle category in the banking industry sector. This shows that the performance of Sharia KPR is assessed in the